Effect of portable cooling device on thermal comfort of medical protective clothing - Fang Wang; Wenliang Guo; Xianfei Liu; Ye Tian; Jicheng Li; Jun Zhang; Chaowen Deng (Case Studies in Thermal Engineering)
Medical protective clothing is important for maintaining the health and safety of the wearer, but its thermal comfort is poor. To improve the thermal comfort, a portable cooling device was designed and a medical protective clothing cooling system was constructed using this device. Through simulations, the actual cooling capacity of the portable cooling device was studied at various temperatures; the micro-environment temperature variation rule for medical protective clothing based on the cooling device was explored under different temperatures and activity intensities, and the cooling system's effect on the wearer's skin temperature was clarified. The results show that the temperature difference between the inlet and outlet of the portable cooling device is maintained at approximately 13 °C under various temperatures, the cooling power is approximately 31.2 W. After cooling system operation for 2 h, the micro-environment temperature and average skin temperature maximum drops are 6.0 °C and 5.6 °C, respectively. The system can reduce the protective clothing's micro-environment temperature and the human skin temperature effectively under various environmental temperature and activity intensity conditions. Which are of significance for verification of the feasibility of a new concept for cooling system design and the resulting improvement in the thermal comfort of medical protective clothing.